An evaluation of Project Rugby Week 1990 for high school boys relating to interpersonal relationships - Paterson, Andrew C.(Andrew Charles) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Human movement studies) -- University of Stellenbosch, 1991.